Перевозбуждение примитивной личности: роман / Е. Н. Вильмонт - Вильмонт Екатерина Николаевна (АСТ, 2014)
Экземпляры: ф.18 (20161125) / Инвентарный номер: 53822 / Цена: / Сис.шифр: Р2 / Авт.знак: В 46 / ББК: 84(2Pос=Рус)6-44